2009
DOI: 10.1124/mol.109.055699
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the CYP3A4 and CYP3A7 Promoters by Members of the Nuclear Factor I Transcription Factor Family

Abstract: Despite the established interindividual variability and ontogeny of the CYP3A enzymes, the most abundant phase I drug-metabolizing enzymes in human liver and intestine, the mechanisms that regulate basal expression remain poorly understood. Electrophoretic mobility shift assays using nuclear proteins extracted from human prenatal and postnatal liver samples identified multiple, developmentally distinct nuclear factor I (NFI)-containing protein complexes from human liver bound to sequences from the CYP3A4 (Ϫ243… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…3C), HNF3b does not bind, whereas YY1 is capable of binding adjacent sequences of the CYP3A4 promoter. In addition, we have shown that members of the NF1 family bind to the region of the CYP3A7 proximal promoter that is differentially methylated during development as well as to the similar sequences from the CYP3A4 promoter (Riffel et al, 2009); however, members of the NF1 transcription factor family differentially affect the activity of the CYP3A4 and CYP3A7 proximal promoters in reporter assays in transiently transfected HepG2 cells whereby the transcriptional activity of the CYP3A4 promoter is increased by members of the NF1 family and the transcriptional activity of the CYP3A7 proximal promoter is decreased (Riffel et al, 2009).…”
Section: Downloaded Frommentioning
confidence: 99%
“…3C), HNF3b does not bind, whereas YY1 is capable of binding adjacent sequences of the CYP3A4 promoter. In addition, we have shown that members of the NF1 family bind to the region of the CYP3A7 proximal promoter that is differentially methylated during development as well as to the similar sequences from the CYP3A4 promoter (Riffel et al, 2009); however, members of the NF1 transcription factor family differentially affect the activity of the CYP3A4 and CYP3A7 proximal promoters in reporter assays in transiently transfected HepG2 cells whereby the transcriptional activity of the CYP3A4 promoter is increased by members of the NF1 family and the transcriptional activity of the CYP3A7 proximal promoter is decreased (Riffel et al, 2009).…”
Section: Downloaded Frommentioning
confidence: 99%
“…Recent data demonstrate that cytochrome CYP3A4 is functionally expressed at the drug resistant, epileptic BBB [23,24]. CYP3A4 oxidizes a large group of xenobiotics, including first generation AEDs [31,34,35]. CYP3A isoforms in humans include 3A3, 3A4, 3A5 and 3A7, sharing at least 85% amino acid sequence homology [36].…”
Section: New Vistas On Drug Biotransformation: Brain P450 Enzymesmentioning
confidence: 99%
“…CYP3A7 is the dominant isoform in these cells compared with CYP3A4 in the human adult liver. Thus, HepG2 cells possess a phenotype most similar to that of the fetal liver (29,30). Although less suitable for predicting effects on metabolism in humans, HepG2 cells provide a system that is easy to handle and reproducible, and thus suitable for the investigation of gene regulation.…”
Section: Discussionmentioning
confidence: 99%
“…pregnane X receptor (PXR; -362/+53) (33), constitutive androstane receptor (CAR) (34), nuclear factor I (-243/-220) (29), differentially expressed in chondrocyte 1 (35) and hepatocyte nuclear factor 4a (HNF4a) (36) have been reported to account for a component of CYP3A4 inter-individual variability.…”
Section: A B a Bmentioning
confidence: 99%